Investment analysis and portfolio management - Reilly, Frank K.; Brown, Keith C. (Australia : Thomson / South-Western, 2003)
Business
Keywords: Portfolio management; Investment; Commom stocks; Derivative markets; Asset management; Global market; Security market; Capital markets; Stock market